Tissue Fatty Acid Profile is Differently Modulated from Olive Oil and Omega-3 Polyunsaturated Fatty Acids in ApcMin/+ Mice - Tutino, Valeria; Caruso, Maria G.; De Leonardis, Giampiero; De Nunzio, Valentina; Notarnicola, Maria (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background: Fatty acid profile can be considered an appropriate biomarker for investigating the relations between the patterns of fatty acid metabolism and specific diseases, as cancer, cardiovascular and degenerative diseases. Objective: Aim of this study was to test the effects of diets enriched with olive oil and omega-3 Polyunsaturated Fatty Acids (PUFAs) on fatty acid profile in intestinal tissue of ApcMin/+ mice. Method: Three groups of animals were considered: control group, receiving a standard diet; olive oilgroup, receiving a standard diet enriched with olive oil; omega-3 group, receiving a standard diet enriched with salmon fish. Tissue fatty acid profile was evaluated by gas chromatography method. Results: Olive oil and omega-3 PUFAs in the diet differently affect the tissue fatty acid profile. Compared to control group, the levels of Saturated Fatty Acids (SFAs) were lower in olive oil group, while an increase of SFAs was found in omega-3 group. Monounsaturated Fatty Acids (MUFAs) levels were enhanced after olive oil treatment, and in particular, a significant increase of oleic acid levels was detected; MUFAs levels were instead reduced in omega-3 group in line with the decrease of oleic acid levels. The total PUFAs levels were lower in olive oil respect to control group. Moreover, a significant induction of Saturation Index (SI) levels was observed after omega-3 PUFAs treatment, while its levels were reduced in mice fed with olive oil. Conclusion: Our data demonstrated a different effect of olive oil and omega-3 PUFAs on tissue lipid profile in APCMin/+ mice.
Keywords: lipid profile